Incremental impact of community-delivered HPV self-sampling on screening uptake within an active outreach system: A quasi-experimental implementation study in rural Thailand - Jiraporn Butta; Phanthitra Thonghoi; Tipamanee Kesakul; Amawasri Thoopthong; Wongsirirak Butdee; Somthawin Pirakittivorakul; Fuangfah Thongdara; Patchana Hengboriboonpong Jaidee; Manachai Yingklang (PLoS ONE, 2026)
Background Thailand has still not achieved the cervical cancer screening coverage target set by the World Health Organization (WHO). Although HPV self-sampling has been introduced to reduce access barriers, delivery remains largely facility-based, requiring women to attend primary care units during working hours. Community-delivered approaches have been proposed as an alternative; however, evidence comparing strategies within the same service context remains limited. This study aimed to assess the incremental benefit of a community-delivered approach, incorporating structured workshops and same-day sample return, within an already active outreach system, compared with a facility-based approach with similar outreach support, on screening uptake; secondary outcomes included operational feasibility and acceptability. Methods We conducted a quasi-experimental comparative study in a rural subdistrict of Thailand. Eligible women aged 30–60 years were recruited from two villages and allocated at the village level to either a community-delivered approach (CD group) or a facility-based approach with active outreach (FB group). Screening uptake was defined as the return of a completed self-sampling kit and is presented using proportions and 95% confidence intervals. Feasibility and acceptability were also assessed descriptively using process indicators and participant-reported experiences. Results A total of 108 participants were enrolled, with 106 included in the primary analysis. Screening uptake was 52% (28/54; 95% CI: 42% to 61%) in the CD group and 35% (18/52; 95% CI: 26% to 45%) in the FB group. The observed absolute difference was 17% (95% CI: −1% to 34%). All returned samples were adequate for HPV testing. Participant-reported confidence, usability, and overall experience with self-sampling were favorable and similar across groups. Conclusions HPV self-sampling was operationally feasible and acceptable under both delivery approaches in this rural Thai setting. Screening uptake was numerically higher in the community-delivered group; however, the confidence interval included no difference, indicating uncertainty in the direction and magnitude of effect. These findings are suggestive but inconclusive evidence. Further adequately powered studies with rigorous implementation evaluation are needed, particularly to optimize service delivery, including increasing flexibility in scheduling, strengthening implementation fidelity, and evaluating workforce and cost implications, to better determine effectiveness and scalability. Trials Registration: Thai Clinical Trials Registry (TCTR): TCTR20241231010.